2013
DOI: 10.1007/s13361-013-0694-x
|View full text |Cite
|
Sign up to set email alerts
|

Protonated Dipeptide Losses from b5 and b4 Ions of Side Chain Hydroxyl Group Containing Pentapeptides

Abstract: Abstract. In this study, C-terminal protonated dipeptide eliminations were reported for both b 5 and b 4 ions of side chain hydroxyl group (-OH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In our previous studies on the fragmentation reactions of E/D containing model peptides [21,22], we detected [M+H+14] + ions in the full scan mass spectra (MS). Further MS/MS experiments have revealed that the side chains of E/D residue were methylated.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies on the fragmentation reactions of E/D containing model peptides [21,22], we detected [M+H+14] + ions in the full scan mass spectra (MS). Further MS/MS experiments have revealed that the side chains of E/D residue were methylated.…”
Section: Introductionmentioning
confidence: 99%